APLIKASI TEPUNG DAUN TURI HASIL FERMENTASI DALAM PAKAN BUATAN TERHADAP PERTUMBUHAN BENIH IKAN NILA SRIKANDI (Oreochromis aureus x niloticus) - Muhammad Rasyid Ridho; Hayati Soeprapto; M Bahrus Syakirin (Fakultas Perikanan Universitas Pekalongan, 2017)
The aim of this research is to determine the effect of fermented flour turi leaves in artificial feed on the growth of Srikandi niloticus fish seed (Oreochromis aureus x niloticus). This research was conducted on Desember 5, 2016 to Januari 5, 2017 in the Laboratory of Brackish Water, Faculty of Fisheries, Pekalongan University. The research method used experimental methods with Complete Random Design (CRD), consisting of 4 treatments and 4 replications. The feed used is artificial feed, whcih added turi leaves fermented flour with different precentages 0 %, 5 %, 10 %, and 15 %. The fish used are Srikandi niloticus fish seed, sized 5-7 cm, stocked in the aquarium, with density of 1 fish/L. The parameters observed were the growing biomass, the survival rate (SR), and the quality of water as supporting data. The results of this research showed that the use of fermented flour turi leaves in artificial feed, affect the growth of Srikandi niloticus fish seed (F count (80,53)> F table (5,96)). The use of fermented flour turi leaves gave the highest yield to the biomass growth rate of Srikandi niloticus fish seed on a treatment equal to 7,33 grams. The results of polynomials orthogonal analysis produced the forms quadratc equation Y = 3,28 + 0,54 X – 0,02 X2 (R2 = 0,78), where X is the percentage of turi leaves fermented flour addition in artificial feed and Y is the growth of Srikandi niloticus fish seed biomass. Based on those equation, the result obtained maximum value X = 12,43 % of the total weight percentage of the feed additions, and maxmimum value Y = 6,64 grams. The survival rate of Srikandi niloticus fish seed during the research reached 100 %. The water quality research is feasible for media maintenance of Srikandi niloticus fish, that is temperature 26 – 29o C, pH 6.7 – 7.8, DO 6 mg/l.Keywords: Niloticus, Turi Leaves Fermented Flour.